OCULAR PERFUSION PRESSURE AND CHOROIDAL THICKNESS IN CENTRAL SEROUS CHORIORETINOPATHY AND PIGMENT EPITHELIOPATHY. Issue 1 (January 2019) - Yun, Cheolmin; Han, Ji Yun; Cho, Sungwon; Hwang, Soon-Young; Kim, Seong-Woo; Oh, Jaeryung
Abstract : Purpose: To investigate ocular perfusion pressure (OPP) in patients with central serous chorioretinopathy (CSC) and pigment epitheliopathy (PE). Methods: In this retrospective study, we included patients with acute idiopathic unilateral CSC and age- and sex-matched normal controls. The patients with CSC were classified into two groups according to the PE presence on their fellow eyes. We compared OPP among CSC patients with or without PE and normal controls. Results: Among a total of 47 patients with CSC, 21 were classified into the PE group and 26 into the non-PE group. The mean OPP (±SD) of CSC and fellow eyes in the PE group (50.02 ± 4.98 and 50.83 ± 4.12 mmHg, respectively) was greater than that in the non-PE group (43.69 ± 6.88 and 44.0 ± 6.57 mmHg, respectively) and normal controls (45.64 ± 8.73 mmHg) (all, P < 0.05). The mean macular choroidal thickness of CSC and fellow eyes in the PE group (344.4 ± 31.8 and 310.1 ± 37.0 μ m, respectively) was thicker than that in the non-PE group (318.5 ± 43.8 and 282.8 ± 36.1 μ m, respectively) (all, P < 0.05). Greater macular choroidal thickness and higher OPP were associated with PE ( P = 0.002 and P = 0.003). Conclusion: Forty-five percent of the patients with acute unilateral CSC had PE in their fellow eyes. Increased OPP may influence the development of bilateral CSC characteristics. Abstract : Supplemental Digital Content is Available in the Text.Among patients with acute idiopathic unilateral central serous chorioretinopathy, 45% showed pigment epitheliopathy in their fellow eyes. Greater ocular perfusion pressure and choroidal thickness might contribute to the bilateral characteristics of central serous chorioretinopathy.